33rd AIAA Applied Aerodynamics Conference 2015
DOI: 10.2514/6.2015-3384
|View full text |Cite
|
Sign up to set email alerts
|

Aerodynamic Effects of Roughness on Wind Turbine Blade Sections

Abstract: This work describes an investigation into the aerodynamic effects of the painted surface roughness of manufactured wind turbine blades. Fetches of wavy, orange-peel type roughness typical of new blades were applied to two DU96-W-180 models of chord lengths 0.46-m and 0.80-m. Lift, drag and transition location were measured at chord Reynolds Numbers ranging from 1.5x10 6 to 3.0x10 6 . For all cases, the results showed that with increasing roughness Reynolds Number the lift decreases, the drag increases and tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…This technique also showed a small amount of model bending (<2 mm). Previous studies with this model [12,13] have shown that boundary layer transition and other aerodynamic qualities do not vary in the span (z) direction, which suggests that this model bending does not affect the model aerodynamics. However, the bending is enough to bias the single laser angle of attack measurement.…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…This technique also showed a small amount of model bending (<2 mm). Previous studies with this model [12,13] have shown that boundary layer transition and other aerodynamic qualities do not vary in the span (z) direction, which suggests that this model bending does not affect the model aerodynamics. However, the bending is enough to bias the single laser angle of attack measurement.…”
Section: Resultsmentioning
confidence: 83%
“…For this work, a 0.8 m chord DU96-W-180 airfoil model was installed into the test section shown in Figure 1b. This model, which has been used in a number studies at the VT SWT [12,13], was constructed at Virginia Tech by the Aerospace and Ocean Engineering Machine Shop. The model is constructed of 50-mm thick CNC-machined aluminum laminates.…”
Section: Methodsmentioning
confidence: 99%